(untitled) - Jones, H. R. N. (Oxford,New York, 2000)
This book is an introductory text on radiation heat transfer aimed at undergraduate and postgraduate students working in an engineering environment, who have no prior knowledge of the subject. It starts from the basic physical principles of thermal radiation, and then goes on to develop methods for the calculation of view factors, rates of heat transfer between surfaces, effects of intervening gases, and the treatment of combined modes of heat transfer. It applies these methods to a number of practical engineering examples, including heat transfer in furnaces, techniques for the measurement of temperature, and radiation from particles in combustion gases. The text works from a student's point of view, and is based firmly in the tradition of hand calculation, as commonly encountered in university teaching programmes.
Keywords: Heat,Heat engineering,Công nghệ nhiệt; Radiation and absorption